Global Emergency Medicine: A Review of the Literature From 2013. (8th July 2014) - Becker, Torben K.; Jacquet, Gabrielle A.; Marsh, Regan; Schroeder, Erika D.; Foran, Mark; Bartels, Susan; Duber, Herbert C.; Cockrell, Hannah; Levine, Adam C.; the Global Emergency Medicine Literature Review (GEMLR) Group; Cone, David C.; A‐Rahman, Nada; et al.
Abstract Objectives The Global Emergency Medicine Literature Review (GEMLR) conducts an annual search of peer‐reviewed and grey literature relevant to global emergency medicine (EM) to identify, review, and disseminate the most important new research in this field to a worldwide audience of academics and clinical practitioners. Methods This year 8, 768 articles written in six languages were identified by our search. These articles were distributed among 22 reviewers for initial screening based on their relevance to the field of global EM. An additional two reviewers searched the grey literature. A total of 434 articles were deemed appropriate by at least one reviewer and approved by an editor for formal scoring of overall quality and importance. Results Of the 434 articles that met our predetermined inclusion criteria, 65% were categorized as emergency care in resource‐limited settings, 18% as EM development, and 17% as disaster and humanitarian response. A total of 24 articles received scores of 18 or higher and were selected for formal summary and critique. Interrater reliability for two reviewers using our scoring system was good, with an intraclass correlation coefficient of 0.63 (95% confidence interval = 0.55 to 0.69). Infectious diseases, trauma, and the diagnosis and treatment of diseases common in resource‐limited settings represented the majority of articles selected for final review. Conclusions In 2013, there were more emergency care in resource‐limited settings articles, while the number of disaster and humanitarian response articles decreased, when compared to the 2012 review. However, the distribution of articles selected for full review did not change significantly. As in prior years, the majority of articles focused on infectious diseases, as well as trauma and injury prevention.